Implementation of the Schoolwide Enrichment Model in Italy: A Three-Year Study - Milan, Lara; Reis, Sally; Murat Cebeci, Sukru; Maraschi, Paola (International Journal for Talent Development and Creativity, 2023)
In this article, we describe the positive outcomes emerging from a three-year implementation of the Schoolwide Enrichment Model (SEM) in the first Italian implementation of the model. Both students and teachers benefitted from the positive experience of the SEM educational approaches to talent development which provides an educational experience that other Italian and European schools may wish to adapt to promote talent development. The SEM benefits all students with some forms of enrichment and simultaneously provides educational opportunities for academically talented students in Italy.